2022
DOI: 10.1111/aman.13798
|View full text |Cite
|
Sign up to set email alerts
|

“Nature” and territories as victims: Decolonizing Colombia's transitional justice process

Abstract: Across different national contexts, liberal legal frameworks have primarily focused on war crimes and violence against human victims as violations of human rights and international law. In Colombia, there is growing legal recognition that “nature” and territories are also casualties of war, requiring punitive sanctioning and reparative treatment in the country's transitional justice process. This article examines how local communities inhabiting the epicenters of violence, along with officials responsible for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 73 publications
0
1
0
Order By: Relevance
“…In addition, local communities such as Bissu experience cultural and religious struggles where there are clashes in the form of contestation and resistance to their presence in society (Adnan, 2018; 29 . As indicated by oleh 30 showed that local communities living in the centres of violence in Colombia, together with the governments that should be responsible for the implementation of justice, create tensions because of the power they have.…”
Section: Local Communitymentioning
confidence: 99%
“…In addition, local communities such as Bissu experience cultural and religious struggles where there are clashes in the form of contestation and resistance to their presence in society (Adnan, 2018; 29 . As indicated by oleh 30 showed that local communities living in the centres of violence in Colombia, together with the governments that should be responsible for the implementation of justice, create tensions because of the power they have.…”
Section: Local Communitymentioning
confidence: 99%